Analisis Determinan Kegagalan Imunisasi Dasar Lengkap dan Zero Dose serta Efektivitas Strategi Imunisasi Kejar dalam Mitigasi Kejadian Luar Biasa Penyakit yang Dapat Dicegah Dengan Imunisasi: Analysis of Determinants of Complete Basic Immunization Failure and Zero Dose, and the Effectiveness of Catch-Up Immunization Strategies in Mitigating Extraordinary Events of Vaccine-Preventable Diseases - Setyowati, Lisus; Perwiraningrum, Dhyani Ayu; satya, Malinda Capri Nurul; Rahmawati, Ira (Chakra Brahmanda Lentera Institute, 2026)
Complete Basic Immunization (CBI) coverage refers to the percentage of children who have received all scheduled basic immunizations according to the national program, usually before 12 months of age. Cumulative CBI coverage in Jember Regency as of July 2025 remains low, reaching only 39.76% of the target. This study aimed to analyze the low CBI coverage and the high proportion of Zero Dose (ZD) children as key determinants of Extraordinary Events (Outbreaks) of Vaccine-Preventable Diseases (VPDs) in Jember Regency, and to evaluate the effectiveness of catch-up immunization interventions. A descriptive-analytical approach was employed using secondary immunization program data from Jember Regency between January 2024 and July/August 2025, obtained from the local Health Office. Epidemiological analysis revealed suspected and confirmed cases of diphtheria and measles-rubella (MR), including the declaration of a measles outbreak in seven community health centers (Puskesmas) in 2025. Low coverage was influenced by a complex set of risk factors, including vaccine hesitancy among families and structural challenges. Catch-up immunization was a critical strategy to close immunity gaps, with 1,129 children immunized with DPT-HB Hib as of August 2024, from a target population of 3,464. These findings highlight the need for integrated interventions targeting the root causes of vaccine hesitancy, improving tracking of migrant children, and optimizing cross-sectoral collaboration to achieve herd immunity and the elimination of VPDs.